Analysis of Microscopic Blood Samples for Detecting Malaria - Saw Hui, Ann (2013)
Malaria is a mosquito-borne disease and it has been affecting millions of people worldwide since decades ago. The conventional method in diagnosing the blood disease is by using manual visual examination of microscopy blood smears. However, a computer-assisted system can be designed to assist in malaria diagnosis by employing image processing, analysis and feature recognition algorithm. In terms of enhancing image for analysis, this study explores on a new approach by averaging results of two filters. In order to evaluate the performance of the proposed method, the image was further clustered by using K-Means, Expectation Maximization (EM) and Otsu’s threshold algorithm .